4 × 4 ultra wideband Butler Matrix for switched beam array - Abang Zaidel, Dyg Norkhairunnisa (2015)
In this paper, a new design of 4×4 ultra wideband (UWB) Butler Matrix for switched beam array is introduced. Multilayer technology is employed into the designed technique in order to develop a compact size Butler Matrix for UWB applications. The new proposed UWB Butler Matrix design offers two main contributions, which are an improvement of 18.6 % wider bandwidth compared to available UWB Butler Matrix and 31.1 % size reduction compared to planar configurations of Butler Matrix. Simulation results are obtained by using Computer Simulation Technology Microwave Studio 2012. All measurement of S-parameters and phase differences performances are performed by using a vector network analyzer. Meanwhile, the measurement beam directions of the UWB Butler Matrix are steered towards a particular direction by switching the input port accordingly. The switched beam antenna array system shows that four orthogonal beams are produced at four different directions. All measurement results show very good agreement with the simulation results.